2014
DOI: 10.5551/jat.23929
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Mitochondria ROS in Atherosclerotic Lesions: Causation or Association?

Abstract: Mitochondrial-derived reactive oxygen species (mtROS) is one of the major sources of cellular ROS, and excessive mtROS is associated with atherosclerosis progression in both human and mouse models. This review aims to summarize the most recent studies showing the existence, the causes and pathological consequences of excessive mtROS in atherosclerosis. Despite numerous association and causation studies demonstrating the importance of mtROS in atherosclerosis progression, the failure of antioxidant therapy in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 82 publications
(95 reference statements)
1
42
0
Order By: Relevance
“…We found that the atherosclerotic lesion area and its macrophage content in cross-sections of the aortic root were increased significantly in Ogg1 −/− Ldlr −/− mice compared with Ldlr −/− controls (Figure 3B and C). The critical features of advanced atheromatous lesions are increases in TUNEL positive apoptotic cells and necrotic area 35, 36 , and a corresponding decrease in collagen content. OGG1 deficiency resulted in a significant increase in both TUNEL positive cells and necrotic area, as well as a decrease in collagen content in their lesions (Figure 3D–F, Supplemental Figure IIB).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the atherosclerotic lesion area and its macrophage content in cross-sections of the aortic root were increased significantly in Ogg1 −/− Ldlr −/− mice compared with Ldlr −/− controls (Figure 3B and C). The critical features of advanced atheromatous lesions are increases in TUNEL positive apoptotic cells and necrotic area 35, 36 , and a corresponding decrease in collagen content. OGG1 deficiency resulted in a significant increase in both TUNEL positive cells and necrotic area, as well as a decrease in collagen content in their lesions (Figure 3D–F, Supplemental Figure IIB).…”
Section: Resultsmentioning
confidence: 99%
“…Ogg1 deficiency resulted in a substantial increase in oxidized mtDNA, which resulted in NLRP3 activation, IL-1β secretion, and accelerated atherosclerosis. Several reports have investigated the causes and pathological consequences of excessive mtROS in atherosclerosis in both humans and mouse models 36, 58 . It is reported that 8-OH-dG accumulation in mtDNA is increased 20-fold in livers of Ogg1 −/− mice compared to WT mice 59 .…”
Section: Discussionmentioning
confidence: 99%
“…ROS production plays pivotal roles in mediating endothelial cell apoptosis and regulating the development of atherosclerosis [11], while NADPH oxidase is a major source of vascular ROS production, and the enzyme complex of NADPH oxidases are considered a major source of superoxide anion formation [12]. In addition, NADPH oxidase is also heavily involved in endothelial apoptosis [13].…”
Section: Resultsmentioning
confidence: 99%
“…Pro-and antioxidant balance may be important in the development of atherosclerosis. Enhanced oxidative stress is reportedly related to cardiovascular risk with endothelial dysfunction and LDL oxidation [10][11][12] . Estrogen can act as an antioxidant, and postmenopausal estrogen therapy has been reported to inhibit LDL oxidation 13,14) .…”
Section: Laboratory Analysismentioning
confidence: 99%